Implementasi Nilai-Nilai Akhlak Dalam Layanan Bimbingan Kelompok Untuk Mengatasi Bullying Pada Siswa SMP Al-Furqan Jember - Kunzita Lazuardi; Usriyah, Lailatul (Pendidikan Islam Pascasarjana IAIN Jember, 2025)
Bullying is a serious problem in educational settings that significantly impacts students' psychological, social, and academic development. Various interventions have been developed, but most still rely on conventional psychological approaches that do not fully consider local moral values. This study aims to develop and test the effectiveness of a moral values-based group guidance service model in preventing and addressing bullying at Al-Furqan Junior High School in Jember. This study used a qualitative approach with a case study method through in-depth interviews, participant observation, and documentation studies. The results showed that the integration of moral values ​​such as empathy, mutual respect, trustworthiness, and social responsibility significantly changed the way students understood and interpreted bullying behavior. Students not only stopped teasing but also internalized moral shame (al-ḥayā’) and religious awareness regarding the impact of their behavior. Supporting programs such as anti-bullying drama performances, anti-bullying declarations, and the formation of Character Ambassadors reinforced this transformation through emotional experiences and collective commitment. In addition, moral-based group guidance services increase empathy capacity, encourage role changes from bystander to upstander, and create a safer and more civilized school culture.